2022
DOI: 10.3389/fenvs.2022.985101
|View full text |Cite
|
Sign up to set email alerts
|

Green production information transparency and online purchase behavior: Evidence from green agricultural products in China

Abstract: The “lemon effect,” which is the result of information asymmetry and barriers to trust, poses serious challenges to the sustainable development of green agricultural products. Therefore, enhancing consumers’ trust is critical to maintain sustainable purchasing behavior. Information transparency has been widely attention as a marketing tool, and previous research related to agricultural products has focused on the visible information. Based on signaling theory, this study takes an invisible information perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 81 publications
2
14
0
Order By: Relevance
“…Sellers provide information on the quality of water in the production of green produce to ensure food safety and compliance with green product quality standards, thereby product environment transparency increases consumers' trust in online sellers, in line with previous studies (Han and Yan, 2019;Castro-González et al, 2021;Giacomarra et al, 2021). The model results show that consumers' competence trust significantly and positively affects online consumers' purchase behavior (β = 0.752, p < 0.001) and benevolence trust also significantly and positively affects online consumers' purchase behavior (β = 0.139, p < 0.05), and H3a and H4 are supported, which indicates that online consumers' trust can enhance their green agricultural products purchase behavior (Mohan et al, 2021;Fu et al, 2022). Interestingly, we found that competence trust has a stronger effect on online consumers' purchasing behavior compared to benevolence trust.…”
Section: The Effect Of Water Information Transparency On Online Consu...supporting
confidence: 89%
See 4 more Smart Citations
“…Sellers provide information on the quality of water in the production of green produce to ensure food safety and compliance with green product quality standards, thereby product environment transparency increases consumers' trust in online sellers, in line with previous studies (Han and Yan, 2019;Castro-González et al, 2021;Giacomarra et al, 2021). The model results show that consumers' competence trust significantly and positively affects online consumers' purchase behavior (β = 0.752, p < 0.001) and benevolence trust also significantly and positively affects online consumers' purchase behavior (β = 0.139, p < 0.05), and H3a and H4 are supported, which indicates that online consumers' trust can enhance their green agricultural products purchase behavior (Mohan et al, 2021;Fu et al, 2022). Interestingly, we found that competence trust has a stronger effect on online consumers' purchasing behavior compared to benevolence trust.…”
Section: The Effect Of Water Information Transparency On Online Consu...supporting
confidence: 89%
“…The online seller publicly provides information about the quality of the soil used in the production of green agricultural products Liu (2013), Fu et al (2022) The seller provides generally consistent information about the quality of the soil used in the production of green agricultural products on various channels…”
Section: Soil Information Transparencymentioning
confidence: 99%
See 3 more Smart Citations